2008
DOI: 10.1210/en.2008-1183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Small-Molecule Glucokinase Activator on Glucose Metabolism and β-Cell Mass

Abstract: We investigated the effect of glucokinase activator (GKA) on glucose metabolism and beta-cell mass. We analyzed four mouse groups: wild-type mice and beta-cell-specific haploinsufficiency of glucokinase gene (Gck(+/-)) mice on a high-fat (HF) diet. Each genotype was also treated with GKA mixed in the HF diet. Rodent insulinoma cells and isolated islets were used to evaluate beta-cell proliferation by GKA. After 20 wk on the above diets, there were no differences in body weight, lipid profiles, and liver trigly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
68
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 43 publications
9
68
1
Order By: Relevance
“…In a study of beta cell function, it was reported that a GKA stimulated insulin secretion in a Ca 2+ -dependent manner in rodent islets and MIN6 cells [13], and we and others have reported that GKAs promoted beta cell proliferation and increased production of IRS2 [11,14], which is critically required for beta cell growth and survival [3,[15][16][17]. However, the exact mechanisms by which GKAs stimulate beta cell function and proliferation are largely unknown.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study of beta cell function, it was reported that a GKA stimulated insulin secretion in a Ca 2+ -dependent manner in rodent islets and MIN6 cells [13], and we and others have reported that GKAs promoted beta cell proliferation and increased production of IRS2 [11,14], which is critically required for beta cell growth and survival [3,[15][16][17]. However, the exact mechanisms by which GKAs stimulate beta cell function and proliferation are largely unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Since the report by Grimsby et al in 2003 [5], several glucokinase activators (GKAs) have been developed, and these have been shown to lower blood glucose in several animal models of type 2 diabetes [5][6][7][8][9][10][11][12]. In a study of beta cell function, it was reported that a GKA stimulated insulin secretion in a Ca 2+ -dependent manner in rodent islets and MIN6 cells [13], and we and others have reported that GKAs promoted beta cell proliferation and increased production of IRS2 [11,14], which is critically required for beta cell growth and survival [3,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest in the development of GKAs as potential therapies for type 2 diabetes because glucokinase activity plays an essential role in glucose-sensing by beta cells and glucose metabolism by hepatocytes [2][3][4][5]. The importance of this enzyme in glucose homeostasis was first widely recognised with the discovery of clinical syndromes resulting from loss-of-function and gain-of-function glucokinase gene mutations [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Various lines of indirect evidence suggest that pharmacological interventions that augment glucokinase activity may favour mechanisms that slow or prevent beta cell loss [22,23] or promote beta cell proliferation in vivo [3,[24][25][26][27]. The present experiments were undertaken to address an ongoing need for data to test and shed further light on this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…In ␤-cells, GK is the glucose sensor that controls the rate of glycolysis, hence insulin secretion, within the physiological range of glucose concentrations (28). Given the pivotal role of GK in glucose homeostasis, small-molecule GK activators (GKAs) were developed that augment GSIS and hepatic glucose utilization (17), thereby improving glucose homeostasis in rodent and human type 2 diabetes (T2D) (3,7,11,13,29,31,33,48). However, although some GKAs may improve ␤-cell survival and GSIS under glucotoxic conditions, the loss of GKA effectiveness during long-term treatment of T2D (22, 47) raises questions about their possible toxicity, e.g., through sustained ␤-cell stimulation.…”
mentioning
confidence: 99%